Different Effects of Double-Pulse TMS of the Posterior Parietal Cortex on Reflexive and Voluntary Saccades - KAPOULA, Zoi; YANG, Qing; Sabbah, Norman; Vernet, marine (Frontiers in Human Neuroscience, 2011)
Gap and overlap tasks are widely used to promote automatic versus controlled saccades. This study examines the hypothesis that the right posterior parietal cortex (PPC) is differently involved in the two tasks. Twelve healthy students participated in the experiment. We used double-pulse transcranial magnetic stimulation (dTMS) on the right PPC, the first pulse delivered at the target onset and the second 65 or 80ms later. Each subject performed several blocks of gap or overlap task with or without dTMS. Eye movements were recorded with an Eyelink device. The results show an increase of latency of saccades after dTMS of the right PPC for both tasks but for different time windows (0-80ms for the gap task, 0-65ms for the overlap task). Moreover, for rightward saccades the coefficient of variation of latency increased in the gap task but decreased in the overlap task. Finally, in the gap task and for leftward saccades only, dTMS at 0-80ms decreased the amplitude and the speed of saccades. Although the study is preliminary and needs further investigation in detail, the results support the hypothesis that the right PPC is involved differently in the initiation of the saccades for two tasks: in the gap task the PPC controls saccade triggering while in the overlap task it could be a relay to the Frontal Eye Fields which is known to control voluntary saccades, e.g. memory-guided and perhaps the controlled saccades in the overlap task The results have theoretical and clinical significance as gap-overlap tasks are easy to perform even in advanced age and in patients with neurodegenerative diseases.